Research on the Impact of Rural Tourism Development on the Economic Benefits of Bama County in Guangxi - Huang Xinye (SHS Web of Conferences)
Bama County, one of the top five tourist spots in Guangxi Zhuang Autonomous Region, began developing rural tourism in 2006. After 17 years of growth, it has become a representative example of rural tourism development for ethnic minorities in Guangxi Zhuang Autonomous Region. To explore the influence mechanism and function of rural tourism in Bama County in the context of rural revitalization, this study collects relevant data on Bama County from 2015 to 2022. The cointegration and Granger causality tests are used to examine the relationship between the number of tourists Bama County receives and its economic impact. The test results show that the fluctuation in the number of tourists visiting Bama County has a significant impact on the county’s tax revenue. Furthermore, based on the research findings, this study offers recommendations for how Bama County can achieve long-term development through rural tourism.